(3GdQO Ydi ef LqhR GdSgh Ydi GdfHj Udi Gddg Ydjg hSdes - (3GdYcHQj, GdMGQKj, GdHZOGOj, GdcQNj, CHh YHO Gddg, GdTjN GdoepajO, eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe, J (B413s ((3GdfLa GdCTQas)
(3ChdgG (B:s
(3GdMeO ddg (B....(3abO hbaJ CjgG GdCN habc Gddg dejGSQ GdCehQ hhbGfG hEjGc GdeMPhQ Ydi eG cJHJ Hg aj eYfi eG hLOJg dHYV eTGjNc HSfOg Edi GdMSf Hf eMHhH Yf GdQHGWj (B...s
(3BNQgG (B:s
.. (3gPG GdMOjK aj GdMce Ydi GdfHj Udi Gddg Ydjg hBdg HGdZdW hGdfbU hGQJaGY GdYUeI Yfg ef (B... (3dfGbU GdYbd VYja GdQCj bQjH ef Phj GdBaGJ GdeSbWI Yfge GdJcdja (B.s
(3JHUQI GdYfhGf (B:s
(3aj BNQg (B: (3Je LhGH Cgd GdMGFQ ajeG SCdhG Yfg ef Ugh GdfHj Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\21s
(3GdPQjYI (B11 - 144( 1214)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds